Comparative analysis for methods of building digital elevation models from topographic maps using geoinformation technologies - Belenok, Vadim; Velikodsky, Yuriy; Nikolaienko, Oleksandr; Rul, Nataliia; Kryachok, Sergiy; Malik, Tetiana (Geodesy and Cartography, 2021)
The article considers the question of estimating the accuracy of interpolation methods for building digital elevation models using Soviet topographic maps. The territory of the Kursk region of the Russian Federation was used as the study area, because it is located on the Central Russian Upland and characterized by the complex structure of the vertical and horizontal dissection of the relief. Contour lines automatically obtained using a Python algorithm were used as the initial elevation data to build a digital elevation model. Digital elevation models obtained by thirteen different interpolation methods in ArcGIS and Surfer software were built and analyzed. Special attention is paid to the ANUDEM method, which allows to obtain hydrologically correct digital elevation models. Recommendations for the use of one or another method of interpolation are given. The results can be useful for professionals who use topographic maps in their work and deals with the design using digital elevation models.